Architecturetand The Art of Designing (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, architecture and the art of designing and constructing buildings and structures based on the goals and tasks of architecture , modern technical capabilities and aesthetic views of society.